1999
DOI: 10.1590/s0074-02761999000300011
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure of Triatoma sordida (Hemiptera: Reduviidae) Domestic Populations from Bolivia: Application on Control Interventions

Abstract: The genetic population of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…It might indicate the existence of reproductive barrier for the 'S' population. For T. sordida populations collected in different sites in Bolivia, genetic distances were in accordance to the geographic ones (Noireau et al 1999). On the basis of our allozyme data, genetic distances between T. rubrovaria populations were not found to be correlated with geographic distance.…”
Section: Discussionsupporting
confidence: 71%
“…It might indicate the existence of reproductive barrier for the 'S' population. For T. sordida populations collected in different sites in Bolivia, genetic distances were in accordance to the geographic ones (Noireau et al 1999). On the basis of our allozyme data, genetic distances between T. rubrovaria populations were not found to be correlated with geographic distance.…”
Section: Discussionsupporting
confidence: 71%
“…Further studies indicated that structuring within localities was also present, suggesting that the basic population unit is represented by individual households (Breniére et al 1998). Using a similar approach, Noireau et al (1999b) showed that the panmictic unit of Bolivian populations of T. sordida (allozymic group 1) is larger than that reported for T. infestans, with departures from H-W equilibrium detected only between populations located over ∼ 20km apart; this suggested a better dispersal capacity than previously thought for T. sordida (Noireau et al 1999b).…”
Section: Allozyme Electrophoresismentioning
confidence: 69%
“…Further studies indicated that structuring within localities was also present, suggesting that the basic population unit is represented by individual households (Breniére et al 1998). Using a similar approach, Noireau et al (1999b) showed that the panmictic unit of Bolivian populations of T. sordida (allozymic group 1) is larger than that reported for T. infestans, with departures from H-W equilibrium detected only between populations located over ∼ 20km apart; this suggested a better dispersal capacity than previously thought for T. sordida (Noireau et al 1999b).Moreover, low levels of allozyme diversity in Triatominae have been regarded as a possible indication of higher vulnerability to chemical control as insecticide resistance would be less likely to emerge in genetically depauperate insecticide-treated populations (Schofield et al 1995, Guhl and Schofield 1996, Schofield and Dujardin 1997, Dujardin et al 1998a, Monteiro et al 2001). …”
mentioning
confidence: 99%
“…In addition, closely related species, such as R. colombiensis and R. pallescens (Abad-Franch & Monteiro 2005), can be differentiated using this marker (Table), suggesting that the 45S chromosomal localisation of the ribosomal clusters could be an appropriate marker for the recognition and detection of recently diverged species or populations. FISH analyses of R. robustus and/ or Triatoma sordida (Noireau et al 1999) cryptic species could help to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%